2016
DOI: 10.1038/srep33524
|View full text |Cite
|
Sign up to set email alerts
|

A combination hepatoma-targeted therapy based on nanotechnology: pHRE-Egr1-HSV-TK/131I-antiAFPMcAb-GCV/MFH

Abstract: Combination targeted therapy is a promising cancer therapeutic strategy. Here, using PEI-Mn0.5Zn0.5Fe2O4 nanoparticles (PEI-MZF-NPs) as magnetic media for MFH (magnetic fluid hyperthermia) and gene transfer vector for gene-therapy, a combined therapy, pHRE-Egr1-HSV-TK/131I-antiAFPMcAb-GCV/MFH, for hepatoma is developed. AntiAFPMcAb (Monoclonal antibody AFP) is exploited for targeting. The plasmids pHRE-Egr1-HSV-TK are achieved by incorporation of pEgr1-HSV-TK and pHRE-Egr1-EGFP. Restriction enzyme digestion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…When the mass ratio of magnetic NPs to CD44-shRNA was 40 : 1, the former could practically bind with all plasmids in the system (Figure 6(a)) indicating 40 : 1 was an optimal binding ratio. Within 1,4,8,12, and 24 h and 2 d, DNA was released at a large amount. But it was not greatly different between day 3 and day 4, and PEG-MZF-NPs could protect the plasmids and effectively release DNA (Figure 6(b)).…”
Section: Construction and Identification Of Cd44-shrnamentioning
confidence: 99%
See 2 more Smart Citations
“…When the mass ratio of magnetic NPs to CD44-shRNA was 40 : 1, the former could practically bind with all plasmids in the system (Figure 6(a)) indicating 40 : 1 was an optimal binding ratio. Within 1,4,8,12, and 24 h and 2 d, DNA was released at a large amount. But it was not greatly different between day 3 and day 4, and PEG-MZF-NPs could protect the plasmids and effectively release DNA (Figure 6(b)).…”
Section: Construction and Identification Of Cd44-shrnamentioning
confidence: 99%
“…Owing to some special properties such as easy modifiability, good biocompatibility, little immune response, and being easily coupled with other ligands and easily organized with specific cell surface receptors or swallowed up by target cells and high efficiency rate gene transfer, nanoparticles can be made as ideal carriers [3]. Apart from the general functions of a nanocarrier, magnetic nanoparticles can produce a thermal effect in an alternating magnetic field and hence may be used for tumor hyperthermia [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Mn0.5Zn0.5Fe2O4 as vector, Lin et al combined radionuclide, suicide gene, and MFH organically to treat liver cancer. The results indicated an excellent effect, and the tumor inhibition rate of the combined therapy group was remarkably higher than that of any other single therapy [71]. Another research showed that magnetic cAs 2 O 3 /Fe 2 O 3 nanocomposites adopted to thermochemotherapy for hepatoma had an evident higher effect than that of the single thermotherapy and the As 2 O 3 chemotherapy alone and the equivalent dosage of chemotherapeutics was greatly lowed and has few side effects [72].…”
Section: Tumor-targeted Thermotherapy Of Magnetic Nanometer Materialsmentioning
confidence: 98%
“…131 I-antiAFPMcAb was prepared with chloramine-T method according to the previous report. 13 Briefly, 75-μL antiAFPMcAb and 5-μL Na 131 I (~4 mCi) were mixed in pH 7.2 PBS solution, and then chloramine-T was added to the mixture. After 1 minute, the crude product was purified on a PD10 column.…”
Section: Preparation Of 131 I-antiafpmcabmentioning
confidence: 99%